2014
DOI: 10.1111/ecc.12177
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon-patient communication in oncology

Abstract: Little is known about the quality of post‐operative communications following oncological surgery and the satisfaction of patients with the communication process. Thirty‐eight patients who underwent surgery for primary gastrointestinal cancer were interviewed before being discharged from the hospital. The patients' recall of information concerning the surgery, histological diagnosis, post‐operative therapy and treatment goal was assessed. The congruence between the information provided by the surgeons and that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…In one study, 18 surgeons provided adequate information about a procedure's risk, benefits, and alternatives, but did not respond to patients questions well. Another study 19 found that cardiologists' communication regarding implantable cardiac defibrillators was characterized by unclear representation and omission of information, and a study 20 of information provided following surgery for gastrointestinal cancer found incomplete exchange, particularly for patients receiving palliative care. Given the importance of information exchange in shared decision making, this finding highlights a critical area to assess further.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, 18 surgeons provided adequate information about a procedure's risk, benefits, and alternatives, but did not respond to patients questions well. Another study 19 found that cardiologists' communication regarding implantable cardiac defibrillators was characterized by unclear representation and omission of information, and a study 20 of information provided following surgery for gastrointestinal cancer found incomplete exchange, particularly for patients receiving palliative care. Given the importance of information exchange in shared decision making, this finding highlights a critical area to assess further.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research has suggested that older adults often have completed lower levels of education (Bostock & Steptoe, 2012), which has been found to influence recall of information (Wagner, Wuensch, Friess, & Berberat, 2014). Furthermore, health literacy, i.e., "the degree to which individuals can obtain, process, understand, and communicate about healthrelated information needed to make informed health decisions (Berkman, Davis, & McCormack, 2010, p. 16)," declines with age (Baker, Gazmararian, Sudano, & Patterson, 2000), which consequently affects recall negatively (McCray, 2005).…”
Section: Personal Characteristicsmentioning
confidence: 99%
“…Cancer patients often feel overwhelmed by the amount of information they receive during consultations, and they often misunderstand the information that oncologists provide, such as about prognosis and treatment goal . These findings make clear how important it is for oncologists to tailor their information to patients' prior knowledge and to find out whether patients understand what they are being told.…”
Section: Introductionmentioning
confidence: 99%